2019
DOI: 10.1177/2325967119881961
|View full text |Cite
|
Sign up to set email alerts
|

Suture Versus Screw Fixation of Tibial Spine Fractures in Children and Adolescents: A Comparative Study

Abstract: Background:Tibial spine fractures involve an avulsion injury of the anterior cruciate ligament (ACL) at the intercondylar eminence, typically in children and adolescents. Displaced fractures are commonly treated with either suture or screw fixation.Purpose:To investigate differences in various outcomes between patients treated with arthroscopic suture versus screw fixation for tibial spine avulsion fractures in one of the largest patient cohorts in the literature.Study Design:Cohort study; Level of evidence, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
90
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(92 citation statements)
references
References 24 publications
1
90
0
Order By: Relevance
“…This finding could be affected by the small cohort. Nonetheless other studies with large cohorts showed no differences regarding postsurgical arthrofibrosis, instability, range of motion and return to sport [ 10 ]. Furthermore, in our practice, we usually plan prophylactical hardware removal in children, which is not needed in the case of bone suture.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This finding could be affected by the small cohort. Nonetheless other studies with large cohorts showed no differences regarding postsurgical arthrofibrosis, instability, range of motion and return to sport [ 10 ]. Furthermore, in our practice, we usually plan prophylactical hardware removal in children, which is not needed in the case of bone suture.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, only 55% patients accepted to be tested with arthrometers. This is an important drawback in our analysis but is a common issue even in other studies investigating this uncommon injury, where loss to follow-up ranged from 17% to 76% [ 10 , 11 , 12 , 37 ]. However, we believe that no significantly different knee laxity is to be detected between children who were tested and children who were not tested, since we did not find any difference in terms of clinical outcomes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The current literature demonstrates successful outcomes for surgical patients treated with open reduction and internal fixation (ORIF) and those treated with arthroscopic reduction and internal fixation (ARIF), and clinical outcomes are comparable for fractures treated with sutures and screws. 2,3,6 ORIF allows for direct visualization of the fracture. ARIF, while requiring additional knowledge of arthroscopic techniques, adds the benefit of being minimally invasive and allows the surgeon to perform a more complete intra-articular assessment of the knee.…”
mentioning
confidence: 99%
“…However, slippage of the sutures may occur to different degrees during knee exion and extension, which may cause cutting to the tunnel, thereby preventing early functional recovery. 14,15 Internal xation with suture anchors is one of the surgical approaches for treating ACL tibial avulsion fracture. In et al used intraarticular suture anchors to x the fractured bone and obtained a satisfactory clinical e cacy.…”
Section: E Cacy Evaluationmentioning
confidence: 99%